Analysis of steam consumption in the crude palm oil sterilizer during a 90-minute boiling process - Yasir Amani, Yasir Amani; Siregar, M. Ronny Syahputra; Faisal, Faisal; Hidayat, Heindrix (Journal of Mechafa Engineering and Fabrication, 2025)
In crude palm oil production, productivity largely depends on the performance of the sterilizer, particularly the horizontal type that operates using steam pressure. This study aimed to analyze the performance of the sterilizer by observing the boiling process of fresh fruit bunches (FFB) and determining the heat required during a single sterilization cycle. Observations were carried out throughout the sterilization process, with steam pressure monitored using the pressure gauge located on top of the sterilizer vessel. The daily steam requirement varied, with the highest recorded on the 10th day, reaching 1,050 kg of steam for 735 tons of FFB. Interestingly, a higher volume of FFB did not always correspond to a higher steam demand. On average, the sterilization process required 827 kg of steam per ton of FFB over 24 hours. At PT. Perkebunan Nusantara IV PKS Dolok Sinumbah, the horizontal sterilizer operates with a triple-peak system, a boiling time of 90–100 minutes, steam pressure of 2.8–3.2 kg/cm², and temperatures between 120–135 °C. The results indicate that the heat required reached 738,160.5 kcal/s, the latent heat was 7,772,760 kJ, and the total steam consumption amounted to 8,510,920.5 kcal for 30 tons of FFB.